Research on the Design of a Mill-turn Center - Wang, Zhun (Manufacturing Technology Journal, 2018)
Mill-turn center is an advanced CNC machine tool. This paper presents a novel approach to the conceptual design of a mill-turn center. Firstly, the feature model of a mill-turn center is created based on a RW (representative workpiece) in a Top-down way. After that, two concurrent works are studied: the verification model of the machine tool is setup by transforming its finished feature model; the NC programming is done with the help of the technology of CAM (computer-aided manufacturing). Thirdly, the production verifying of the mill-turn center is fulfilled in the NVMS (NC verification manufacturing system). Lastly, the optimum structure dimension of two functional subassemblies and the correct layout of the machine tool can be confirmed with the modification and feedback. This is a universal method and can be used by the designer of CNC machine tool to promote their job target of quality, efficiency and cost.
Keywords: Design of Mill-turn Center; RW; Top-down Design; NVMS; MCS (Machine Coordination System)